If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -10 = 5 + -3b Reorder the terms: -10 + 2b = 5 + -3b Solving -10 + 2b = 5 + -3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3b' to each side of the equation. -10 + 2b + 3b = 5 + -3b + 3b Combine like terms: 2b + 3b = 5b -10 + 5b = 5 + -3b + 3b Combine like terms: -3b + 3b = 0 -10 + 5b = 5 + 0 -10 + 5b = 5 Add '10' to each side of the equation. -10 + 10 + 5b = 5 + 10 Combine like terms: -10 + 10 = 0 0 + 5b = 5 + 10 5b = 5 + 10 Combine like terms: 5 + 10 = 15 5b = 15 Divide each side by '5'. b = 3 Simplifying b = 3
| 12.5x=10.5 | | -6b=-5b+10 | | 2(y-8)=20 | | 7h=4+6h | | (7(x+5)-18)+(3(x-2)+4)= | | 12.3x-9.2=3x-0.7x | | x+(x*1.08)=188000 | | 7(-3+6x)=-21 | | 2x+3=5x-4+7 | | x^4+1500x^2+1250000=0 | | x*23=33 | | 7x=3x+26 | | 8x-(3x-6)=26 | | 7(2x-1)=11x+5 | | 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= | | 5=7-7x | | p^2+4p+4=40 | | 2x-(x+1)= | | (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 | | 17-x=172 | | 70-61x+4x^2=0 | | -3=-6-x | | -24+5x+x^2=0 | | x^3+3x^2-15x=0 | | -24+x^2=0 |